Fetomaternal outcome in pregnancy with oligohydramnios: a prospective study - Talesara, Heena; Shah, Vidhi C. C.; Modi, Dipti A.; Modi, Rahi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Oligohydramnios is defined as amniotic fluid index <5th percentile or 2 standard deviation below the normal amniotic fluid volume. It affects 4% of all the pregnancy. The aim of this study is to evaluate the etiological risk factor of oligohydramnios and to assess their clinical significance and mode of delivery and maternal and perinatal outcome. Methods: This study was conducted at a tertiary health care centre, SSG Hospital, Baroda, from 1st September 2019 to 30th August 2020. It is a prospective study of 200 cases of oligohydramnios with gestational age > 30 weeks. Results: The most common risk factor associated with oligohydramnios was hypertensive disorder of pregnancy (35%) followed by intra uterine growth restriction (31%), preterm rupture of membranes (17%), post-datism (5%) and about 12% were due to idiopathic causes. Among cases majority were primigravida (43%). Lower segment caesarean section was done in 86 cases (43%), and main indication was fetal distress. There was no maternal mortality in the study. NICU admission for low birth weight (26%), pre-maturity (20%), meconium aspiration syndrome (8%), congenital anomalies (8%). Among congenital anomalies, posterior urethral valve had highest incidence (50%) followed by renal agenesis (25%). The neonatal mortality was 5%. Conclusions: Oligohydramnios adversely affects the perinatal outcome. Therefore, it requires meticulous assessment, prompt detection, timely management and treating underlying condition. However, a favourable outcome can be expected by good antenatal and intrapartum surveillance and neonatal care.